Content and Ease of Use Influencing Electronic Medical Record Net Benefits: The Role of Actual Use - Bastianus Alfian Juatmadja; Hosizah Markam; Natsir Nugroho (International Journal of Economics, Management and Accounting, 2026)
The implementation of Electronic Medical Records (EMR) has become an important element in improving healthcare service quality, efficiency, and patient safety in hospitals. However, the benefits of EMR depend not only on system availability but also on the quality of the information provided and how actively the system is used by healthcare professionals. This study aims to analyze the influence of electronic medical record content and perceived ease of use on the net benefits of EMR, with actual system use acting as an intervening variable. The research applied a quantitative approach with a cross-sectional design conducted at RSM Hospital. The population consisted of all general practitioners and specialist doctors working at the hospital, totaling 51 respondents, and the study used a total sampling technique. Data were collected through structured questionnaires measured using a Likert scale and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results show that EMR content and perceived ease of use significantly influence the net benefits of EMR. Both variables also significantly affect the actual use of the system, while actual use significantly influences the benefits obtained. Furthermore, actual use mediates the relationship between EMR content, ease of use, and net benefits, indicating that better information quality and usability can encourage greater system utilization and maximize the advantages of EMR implementation.